Researcb on Enbanced Multi-Hop Broadcast Algoritbm in Vebicular Communications - Haitao Zhao; Hongbo Zhu; Nanjie Liu; Gengxiong Cai (Dianxin kexue)
An enhanced neighbor information-based multi-hop broadcast protocol（ENIMBP）in highway scenarios was proposed, which calculated the forwarding waiting time by using vehicle neighbor information as well as position, speed and direction to select the optimal forwarding vehicle. In order to calculate the forwarding waiting time, ENIMBP employed position information for vehicles which with different distance to the broadcasting vehicle, while used speed and direction in addition for those with the same distance to the broadcasting vehicle. ENIMBP is a good solution to segmentation problem and hidden／exposed node problem in highway scenarios. Simulation results show that ENIMBP can significantly reduce the end to end delay in a sparse network, while maintaining a high packet delivery ratio.